2013
DOI: 10.1093/gerona/glt142
|View full text |Cite
|
Sign up to set email alerts
|

Do ACE Inhibitors Improve the Response to Exercise Training in Functionally Impaired Older Adults? A Randomized Controlled Trial

Abstract: Background.Loss of muscle mass and strength with ageing is a major cause for falls, disability, and morbidity in older people. Previous studies have found that angiotensin-converting enzyme inhibitors (ACEi) may improve physical function in older people. It is unclear whether ACEi provide additional benefit when added to a standard exercise training program. We examined the effects of ACEi therapy on physical function in older people undergoing exercise training.Methods.Community-dwelling people aged ≥65 years… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
76
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 68 publications
(79 citation statements)
references
References 29 publications
2
76
0
1
Order By: Relevance
“…At 20 weeks, both treatment groups increased their walking distance (29.6 m with perindopril versus 36.4 m with placebo, P=0.43). 131 Similarly, there was no difference between groups for the secondary outcomes of quality of life, functional impairment, or handgrip and quadricep strength. 131 A meta-analysis of ACEi therapy in patients with PAD and claudication included 6 randomized controlled trials, including 821 patients.…”
Section: Angiotensin-converting Enzyme Inhibitorsmentioning
confidence: 87%
See 2 more Smart Citations
“…At 20 weeks, both treatment groups increased their walking distance (29.6 m with perindopril versus 36.4 m with placebo, P=0.43). 131 Similarly, there was no difference between groups for the secondary outcomes of quality of life, functional impairment, or handgrip and quadricep strength. 131 A meta-analysis of ACEi therapy in patients with PAD and claudication included 6 randomized controlled trials, including 821 patients.…”
Section: Angiotensin-converting Enzyme Inhibitorsmentioning
confidence: 87%
“…131 Similarly, there was no difference between groups for the secondary outcomes of quality of life, functional impairment, or handgrip and quadricep strength. 131 A meta-analysis of ACEi therapy in patients with PAD and claudication included 6 randomized controlled trials, including 821 patients. 132 Overall, there was an increase in maximum walking distance (mean differences 120.8 m, 95% CI 2.95-238.68, P=0.04), improved pain-free walking distance (P=0.003), but no change in ABI (P=0.11).…”
Section: Angiotensin-converting Enzyme Inhibitorsmentioning
confidence: 87%
See 1 more Smart Citation
“…Drugs targeting the renin-angiotensin system (RAS) pathway, including angiotensin-converting enzyme inhibitors (ACEi) and angiotensin receptor blockers (ARBs), have a long history of research reported to improve physical function (Simon et al 2015;Sumukadas et al 2014;Thornton and Norgren 2011;Burks et al 2011). Several studies have shown that ACE inhibitors improve exercise capacity in both younger and older people with heart failure (Hutcheon et al 2002), and in older fit subjects without apparent heart disease, a trial of ACE inhibitor showed a shift to type 1 muscle fibre type and increased exercise capacity (Sumukadas et al 2007).…”
Section: Discussionmentioning
confidence: 99%
“…30,31 However, in a recent randomized clinical trial, the use of ACE inhibitors did not increase the effect of exercise training, in particular endurance, in older patients with functional impairment. 32 Our findings of a positive association between ACE inhibitors and functional status might be due to the retrospective nature of the study with possible residual confounding but also to the different measure of functional outcome we have used. Indeed, we have evaluated the global functional status with the BI and not the patients' endurance with the 6-min walking test.…”
Section: Discussionmentioning
confidence: 88%